ALDH2*2 and peer drinking in East Asian college students. (2nd November 2017) - O'Shea, Taryn; Thomas, Nathaniel; Webb, Bradley Todd; Dick, Danielle M.; Kendler, Kenneth S.; Chartier, Karen G.
ABSTRACT: Background : The ALDH2*2 allele (A-allele) at rs671 is more commonly carried by Asians and is associated with alcohol-related flushing, a strong adverse reaction to alcohol that is protective against drinking. Social factors, such as having friends who binge drink, also contribute to drinking in Asian youth. Objectives : This study examined the interplay between ALDH2*2, peer drinking, and alcohol consumption in college students. We hypothesized that the relationship between ALDH2*2 and standard grams of ethanol per month would vary based on the level of peer drinking. Methods : Subjects ( N = 318, 63.25% female) were East Asian college students in the United States who reported drinking alcohol. Data were from the freshman year of a university survey that included a saliva DNA sample. ALDH2*2 status was coded ALDH2*2 (+) (A/G and A/A genotypes) and ALDH2*2 (−) (G/G genotype). Peer drinking was students' perception of how many of their friends "got drunk". Results : Main effects of ALDH2*2 (−) and having more friends who got drunk were associated with greater alcohol consumption. The ALDH2*2 × peer drunkenness interaction showed a stronger positive association with alcohol consumption for ALDH2*2 (−) versus ALDH2*2 (+) at increasing levels of peer drunkenness. Follow-up comparisons within each peer drunkenness level identified significantly higher alcohol consumption for ALDH2*2 (−) compared to ALDH2*2 (+) at the all friends got drunk level. Conclusion : There was evidence of a stronger effect for ALDH2*2 (−) compared to ALDH2*2 (+) with greater alcohol use when students were more exposed to peer drinking. Findings contribute to a growing literature on the interrelationships between genetic influences and more permissive environments for alcohol consumption.